DAMPAK PEMBANGUNAN INFRASTRUKTUR JALAN DAN VARIABEL EKONOMI LAIN TERHADAP LUAS LAHAN SAWAH DI KORIDOR EKONOMI JAWA - Puspita Mega Lestari Effendi; Alla Asmara (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2014)
The role of road infrastructure is important for economic activity in Java Economic Corridor. Infrastructure is needed for developing economic activity, but on the other side it decreases the size of agricultural land. This research is analyzing the impact of road infrastructure development and other economic variables on the size of agricultural land in Java Economic Corridor. This research uses panel data model in 6 provinces in Java Economic Corridor 2001-2011. The finding of the research shows that variable length of road (PJ), population density (KP), and a number of large and medium industries (IND) negatively affected the size of agricultural land in Java Economic Corridor.